2013
DOI: 10.1016/j.radonc.2013.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of response to radiotherapy in the treatment of esophageal cancer using stem cell markers

Abstract: Background and purpose: In this study, we investigated whether cancer stem cell marker expressing cells can be identified that predict for the response of esophageal cancer (EC) to CRT. Materials and methods: EC cell-lines OE-33 and OE-21 were used to assess in vitro, stem cell activity, proliferative capacity and radiation response. Xenograft tumors were generated using NOD/SCID mice to assess in vivo proliferative capacity and tumor hypoxia. Archival and fresh EC biopsy tissue was used to confirm our in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 46 publications
4
45
0
Order By: Relevance
“…Recently, Smit et al showed that CD44+/CD24À EC tumor cells contain more in vitro radioresistant properties than CD44+/CD24+ cells. Furthermore, this was confirmed by analysis of archival pre-CRT biopsy material of 27 patients with AC, as none of the 9 complete responders contained CD44+/CD24À tumor cells [29]. The radioresistant properties of tumor cells might be intrinsic to certain tumor subtypes, but might also be induced during radiotherapy by a mechanism called the tumor-bed-effect [30].…”
Section: Discussionmentioning
confidence: 96%
“…Recently, Smit et al showed that CD44+/CD24À EC tumor cells contain more in vitro radioresistant properties than CD44+/CD24+ cells. Furthermore, this was confirmed by analysis of archival pre-CRT biopsy material of 27 patients with AC, as none of the 9 complete responders contained CD44+/CD24À tumor cells [29]. The radioresistant properties of tumor cells might be intrinsic to certain tumor subtypes, but might also be induced during radiotherapy by a mechanism called the tumor-bed-effect [30].…”
Section: Discussionmentioning
confidence: 96%
“…The following human tumor cell lines were used: HCT-15 [34], HT-29 [35] and LoVo [36], colorectal adenocarcinoma; OE-33 [37], esophageal adenocarcinoma; KYSE-30 [38] and OE-21 [37], esophageal squamous carcinoma; MKN-45 [39], gastric adenocarcinoma. A CD44 high subpopulation of HCT-15 was isolated by immunomagnetic sorting, as previously reported [40].…”
Section: Methodsmentioning
confidence: 99%
“…In this context recent studies have shown promising markers such as stem cell markers in oesophageal cancer [44] and microRNAs as predictive biomarkers for response [45]. These findings have not yet been validated and their clinical relevance needs to be further elucidated.…”
Section: Characteristicmentioning
confidence: 99%